Depth sensing indentation analyses of hypereutectic Al-10Ni — XSc (X = 0, 1, 2) alloys - Karakose, Ercan; Kilicaslan, M. Fatih (Springer Science and Business Media LLC, 2017)
Depth sensing indentation analyses of hypereutectic Al-10Ni alloys with different amounts of Sc content were performed to determine the values of elastic modulus, dynamic microhardness, creep rate and elastic recovery rate. Microstructural characterizations were performed by using scanning electron microscopy (SEM), SEM mapping and an X-ray diffractometer. The results revealed that the addition of Sc refined the intermetallic phases of Al and Ni, and led to the formation of two additional intermetallic phases as well, namely Al3Sc and metastable Al9Ni2. The Al-Ni alloys investigated in this work exhibited elastoplastic behavior at room temperature and the addition of Sc influences their elastic-plastic responses to the indentation process. In addition, dynamic microhardness of them exhibited a load-dependent character called the indentation size effect. The addition of Sc considerably improved the values of dynamic microharddness, elastic modulus and elastic recovery rate. It also resulted in a lower creep displacement rate.
Keywords: 13. Climate action